Development of a fruit smoothie with solid albumen of green coconut - Nátali Silva Teixeira; Renata Torrezan; Daniela De Grandi Castro Freitas-Sá; Sérgio Macedo Pontes; Leilson de Oliveira Ribeiro; Lourdes Maria Correa Cabral; Virgínia Martins da Matta (Ciência Rural, 2019)
ABSTRACT: The present study aimed to develop a mixed smoothie drink using the solid albumen of the green coconut in its composition. Smoothie formulations were prepared following an experimental design, setting the solid albumen concentration at 20% and varying the contents of the acerola (Barbados Cherry), pineapple, and coconut water pulps, which corresponded to 80% of the total mass of the product. Response parameters evaluated were vitamin C content, antioxidant capacity, and overall sensory acceptance. Ten formulations were evaluated. The ones that contained higher concentrations of acerola pulp had higher values of bioactive compounds but were not the most sensorially accepted. By means of the desirability function, a final formulation consisted of 52.8% of pineapple, 27.2% of acerola, and 20.0% of solid albumen of green coconut. This new formulation was well accepted, with a grade (score) 7 (“good”). It represents a good nutritional contribution and a source of vitamin C which can contribute to add value to a co-product of the beverage industry.